Pavel Gerdt and the princes’ variations in “Sleeping Beauty”, “The Nutcracker”, and “Swan Lake” - Doug Fullington (Danza e Ricerca, 2022)
By the time Čajkovskij’s trio of ballets — Sleeping Beauty (1890), The Nutcracker (1892), and Swan Lake (1895 redaction) — came to be performed in St. Petersburg, first dancer Pavel Gerdt had given up performing danced solos. Gerdt was nevertheless cast as the male lead in these ballets, and his solos were assigned to other dancers, including female soloists, senior girl students of the Theater School, and a young man who represented a generation that would define a new era of male dancing in ballet. Source material, including choreographic notations made in the Stepanov system, allows for detailed descriptions of these dances. The result of this approach to compensating for Gerdt’s advancing age and physical limitations was a bifurcated collection of premier danseur roles in some of the most enduring works of the era.